2004
DOI: 10.1095/biolreprod.103.021378
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Estrogen Receptor (ER) Isoform Messenger RNA Expression by Different ER Ligands in Female Rat Pituitary1

Abstract: Net estrogen sensitivity in target tissues critically depends on the regulated expression of full-length and alternately processed estrogen receptor (ER) isoforms. However, the molecular mechanisms for the control of pituitary responsiveness to estrogen remain partially unknown. In the present communication, we report the ability of different ligands, with distinct agonistic or antagonistic properties at the ER, to modulate the expression of the transcripts encoding ERalpha and ERbeta isoforms, as well as thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 28 publications
6
29
0
2
Order By: Relevance
“…To confirm that TMX was bioactive at hypothalamic levels, we studied the mRNA levels of estrogen receptor ␤ and progesterone receptor of TMX-treated rats. As previously reported, the mRNA expression of estrogen receptor ␤ (40) and progesterone receptor (41) was increased in the hypothalamus after TMX treatment (online appendix Fig. 2).…”
Section: Resultssupporting
confidence: 84%
“…To confirm that TMX was bioactive at hypothalamic levels, we studied the mRNA levels of estrogen receptor ␤ and progesterone receptor of TMX-treated rats. As previously reported, the mRNA expression of estrogen receptor ␤ (40) and progesterone receptor (41) was increased in the hypothalamus after TMX treatment (online appendix Fig. 2).…”
Section: Resultssupporting
confidence: 84%
“…These results support the hypothesis that the 3 isoform may play a significant physiological role that is under steroidal control. A recent report indicates that endogenous estrogen differentially regulates pituitary expression of mRNAs encoding several ER isoforms with distinct functional properties (Tena-Sempere et al 2004). This, together with our current results, allows us to postulate that interaction of ER protein with its ligand not only activates signaling but also turns on different mechanisms for the fine tuning of uterine responsiveness to estrogen.…”
Section: Figuresupporting
confidence: 80%
“…Estrogens play a pivotal role in the development and maintenance of normal sexual and reproductive functions (Heldring et al, 2007;Muriach et al, 2008). The biological action of estrogens is manifested through two high-affinity estrogen receptors, estrogen receptor alpha and estrogen receptor beta, which belong to the family of the transcription factors, the nuclear receptor super family, and are expressed at different levels in target cells (Greene et al, 1986;Kuiper et al, 1996;Gruber et al, 2004;Tean-Sempere et al, 2004). The research results in pregnant swine reported by Knapczyk (2008) suggest that in the regulation of ovarian function during pregnancy estrogen acts both via ESR1 and ESR2 and these are involved in the process of successful reproduction.…”
Section: Introductionmentioning
confidence: 99%